Genetic polymorphism and frequency study at 15 short tandem repeat loci in the North and East Indian populations for use in personal identification and applications in India - Prabakaran Mathiyazhagan; Thangaraju Palanimuthu; Agasthi Padmanathan (Indonesian Journal of Biotechnology, 2024)
Allele frequency is a crucial factor in estimating the weight of evidence (WoE) for an individual’s involvement in a DNA sample. To determine the allele and genotype frequencies within the populations of the northern and eastern states of India, 15 short tandem repeats (STRs) were used, including Penta E, CSF1PO, D18S51, D7S820, D21S11, TH01, D3S1358, Vwa, FGA, TPOX, D8S1179, D16S539, D13S317, Penta D, and D5S818. The study involved 509 randomly selected individuals, analyzed using the PowerPlex 16 System Kit. Various statistical parameters of forensic significance were calculated using Forensic Statistic Analysis Toolbox (FORSTAT) software, including the typical paternity index (TPI), power of exclusion (PE), matching probability (MP), power of discrimination (PD), polymorphism information content (PIC), and observed (Hobs) and expected heterozygosities (Hexp). The analysis revealed a maximum allele frequency of 0.4282 at TPOX, with a minimum frequency of 0.0009 observed at different loci. FGA was found to be the most polymorphic loci among the 15 loci analyzed in the North and East Indian populations. Furthermore, no divergence from the Hardy‐Weinberg equilibrium (HWE) was observed. The results serve as a valuable source of information for establishing a DNA database for North and East Indian populations, providing essential information for population genetics studies and forensic casework in India.